The Amistad case - Andrey A. Shumakov (Historia provinciae: журнал региональной истории, 2024)
This article is devoted to the study of one of the most significant episodes in the history of American slavery and abolitionism – the United States v. the Amistad case of 1839–41. The story of the slave uprising on the Spanish ship of the same name literally captured American society and became the subject of one of the longest and most resonant court proceedings. The most prominent representatives of American abolitionist movement and political establishment were involved in this process, including former and current US presidents, the Spanish Consul, the British Foreign Minister, and many others. The final verdict of the Supreme Court created the most important precedent in American law, marking another milestone in the cause of emancipation. This topic is quite well covered in Anglo-American historiography, especially among specialists in the field of African American history (Black History), while Soviet and Russian researchers have almost never paid proper attention to it. The present work is meant to fill this gap. The study is built on a broad source base, which includes the materials of judicial proceedings, numerous reports and journalistic publications as well as on available Anglo-American research studies. The author reconstructs the picture of the events of the Amistad mutiny and the subsequent trial, focusing on the identification of causal connections and the characteristics of the main stages of the 1839–41 events. In the last part of the article, the author reflects on the consequences and significance of the Amistad case in African-American and American history.